Espectro de gotas e potencial de deriva de caldas contendo o herbicida 2,4-d amina em misturas em tanque - Mota, Alisson Augusto Barbieri [UNESP] (2015)
The tank mix of pesticides is a common and widespread practice in the world, with advantages such as reducing costs, since the same application operation is optimized to apply two or more products. Another reason for the tank mix, in the case of herbicides, is to increase the spectrum of action on weed control, as the application of different mechanisms of action of herbicides contribute to the reduction of resistant biotypes of selection pressure. However, the tank-mix can result in physical changes in the spray solution, interfering in the droplet spectrum and drift risk. In this context, the aim of this study was to evaluate the droplet spectrum and the potential drift of spray solutions containing 2,4-D herbicide in different tank mix conditions and nozzles models. Were compared eight treatments and a control treatment. Each treatment was represented by a spray solution of the mixture or not between herbicides and adjuvants. The control treatment was a solution containing the 2,4-D herbicide (DMA® 806 BR). All treatments and the control were evaluated in two experiments, one spraying with flat spray extended range nozzle (XR 11003 model) and the other with flat spray air induction nozzle (AI 11003 model). The variables analyzed were droplet spectrum and drift index evaluated through wind tunnel. All results were compared by the confidence interval for differences between the averages at 95% probability and also calculated the correlations between the different variables using the Pearson coefficient at 5% probability. In the evaluations of droplets spectrum and drift index, it was found that the different mixtures had action in these variables. Comparing the results with the control, when sprayed with XR nozzle, all mixtures have reduced the volume median diameter (VMD) and increased the percentage of the volume of droplets with a diameter less than 100 μm (% <100) thus increasing the drift ...